Eccrine poroma of the lower limb in a young adult: a rare clinical presentation with surgical excision and grafting - Kumar, Vivek; Kumar, Jony; Mukul; Tiwari, Shivam; Sadhyan, Saksham; Kulshrestha, Sanyam (International Surgery Journal, 2025)
Eccrine poroma is a rare benign growth arise from the intraepidermal structure of the eccrine sweat glands. They are seen on the palms and soles in elderly and rarely presents on non-volar surfaces or in young adults. Herein this case-report reports a case of a 28-years gentleman with an ulcero-proliferative growth on right leg with no other associated morbidity, managed with wide local excision and split-thickness skin grafting. Final histopathology confirmed eccrine poroma. This case report highlights atypical presentation, importance of histological confirmation, and complete surgical management.